1924-2009 85 Years of the Hellenic Veterinary Medical Society - ANANIADIS, Th. (Journal of the Hellenic Veterinary Medical Society, 2017)
Presentation of Mr Theodoros Kl. Ananiadis for the 85 years of the Hellenic Veterinary Medical Society, during the opening celebration of the 11th Pan-Hellenic Veterinary Congress, «The Athens HILTON» Athens 19-22 March 2009